Effects of a sand running surface on the kinematics of sprinting at maximum velocity - Alcaraz, P.; Palao, J.; Elvira, J.; Linthorne, N. (Biology of Sport, 2011)
Performing sprints on a sand surface is a common training method for improving sprint-specific strength. For maximum specificity of training the athlete`s movement patterns during the training exercise should closely resemble those used when performing the sport. The aim of this study was to compare the kinematics of sprinting at maximum velocity on a dry sand surface to the kinematics of sprinting on an athletics track. Five men and five women participated in the study, and flying sprints over 30 m were recorded by video and digitized using biomechanical analysis software. We found that sprinting on a sand surface was substantially different to sprinting on an athletics track. When sprinting on sand the athletes tended to`sit` during the ground contact phase of the stride. This action was characterized by a lower centre of mass, a greater forward lean in the trunk, and an incomplete extension of the hip joint at take-off. We conclude that sprinting on a dry sand surface may not be an appropriate method for training the maximum velocity phase in sprinting. Although this training method exerts a substantial overload on the athlete, as indicated by reductions in running velocity and stride length, it also induces detrimental changes to the athlete`s running technique which may transfer to competition sprinting.